Gcm counteracts Toll-induced inflammation and impacts hemocyte number through cholinergic signaling - Bazzi, Wael; Monticelli, Sara; Delaporte, Claude; Riet, Céline; Giangrande, Angela; Cattenoz, Pierre B. (Frontiers in Immunology, 2023)
Hemocytes, the myeloid-like immune cells of Drosophila, fulfill a variety of functions that are not completely understood, ranging from phagocytosis to transduction of inflammatory signals. We here show that downregulating the hemocyte-specific Glial cell deficient/Glial cell missing (Glide/Gcm) transcription factor enhances the inflammatory response to the constitutive activation of the Toll pathway. This correlates with lower levels of glutathione S-transferase, suggesting an implication of Glide/Gcm in reactive oxygen species (ROS) signaling and calling for a widespread anti-inflammatory potential of Glide/Gcm. In addition, our data reveal the expression of acetylcholine receptors in hemocytes and that Toll activation affects their expressions, disclosing a novel aspect of the inflammatory response mediated by neurotransmitters. Finally, we provide evidence for acetylcholine receptor nicotinic acetylcholine receptor alpha 6 (nAchRalpha6) regulating hemocyte proliferation in a cell autonomous fashion and for non-cell autonomous cholinergic signaling regulating the number of hemocytes. Altogether, this study provides new insights on the molecular pathways involved in the inflammatory response.